Magnetically responsive dry fluids - Sousa, Filipa L.
Ferrofluids and dry magnetic particles are two separate classes of magnetic materials with specific niche applications, mainly due to their distinct viscosity and interparticle distances. For practical applications, the stability of these two properties is highly desirable but hard to achieve. Conceptually, a possible solution to this problem would be encapsulating the magnetic particles but keeping them free to rotate inside a capsule with constant interparticle distances and thus shielded from changes in the viscosity of the surrounding media. Here we present an example of such materials by the encapsulation of magnetic ferrofluids into highly hydrophobic silica, leading to the formation of dry ferrofluids, i.e., a material behaving macroscopically as a dry powder but locally as a ferrofluid where magnetic nanoparticles are free to rotate in the liquid.